Placement of Dental Implants in Patients Receiving Bisphosphonate Therapy - Levente Palásti; Dóra Iványi; Ferenc Oberna; Márton Kivovics (Hungarian Dental Association, 2019)
Bisphosphonates (BP) are widely used in the therapy of osteoporosis and bone related metastatic lesions. The administration of BPs may lead to necrosis of the jaws (medication related osteonecrosis of the jaw, MRONJ). The aim of our review is to summerise the literature, recommendations, and current position papers on dental implant placement in patients receiving BPs. Materials and Methods Structured search strategy was applied on electronic databases: MEDLINE and Web of Science using the following keywords: "bisphosphonates", "dental implant", and "MRONJ". Scientific publications in Hungarian and English between 2014 and 2019 were identified. Results The initial search resulted in a total of 291 articles. By consensus the authors selected 27 relevant publications to review. According to our review implant success is similar in patients receiving oral BPs and patients not taking BPs. Implant failure and MRONJ is more prevalent in patients receiving intravenous BPs than in patients not receiving iv BP therapy. The current recommendation of the Hungarian Association of Oral and Maxillofacial Surgeons states that both oral and intravenous BP therapy contraindicates dental implant placement because of the high risk of MRONJ. According to our review there is no single biological marker suitable for the prediction of MRONJ. Conclusions Dental implant placement in patients receiving BPs requires risk benefit assessment for every individual case. Success of implantation and development of MRONJ is influenced by methods of BP administration, the medical condition because of which the BPs were prescribed, the duration of BP treatment, and comorbidities that promote the development of MRONJ. Further studies are essential since there are few long terms randomized controlled clinical studies in this field. However, based on international recommendations and position papers it is safe to state that placement of dental implants should be avoided in the oncology patient receiving intravenous BPs. For patients receiving oral BPs for less than four years and have no comorbidities that promote the development of MRONJ dental implant placement is low risk. For patients receiving oral BPs for more than four years or have comorbidities that promote the development of MRONJ dental implant placement may be considered using a drug holiday protocol. However, in these cases it is recommended that patients receive antibiotic prophylaxis for dental implant placement.